Pleasured [large type] - Camp, Candace (Camp, Candace. Secrets of the loch, 2015)
Damon, the earl of Mardoun, is smitten the moment he meets Meg, the village healer -- but she will have none of him, even if he is the most handsome man she's ever laid eyes on. Then Damon's daughter falls gravely ill. Distraught, he turns to Meg for help. As she nurses his beloved daughter back to health, Meg and Damon fall madly in love. Yet they both know an earl must wed a noble bride, and Meg will be no man's mistress . . .